Effect of method of preparation on pioglitazone HCl-Î²-cyclodextrin inclusion complexes - Beloshe, Shrikant P; Chougule, Dhanyakumar D; Shah, Rohit R; Ghodke, Dhananjay S; Pawar, Nagnath D; Ghaste, Rahul P (Asian Journal of Pharmaceutics (AJP), 2014)
Pioglitazone HCl is an antidiabetic agent with poor aqueous solubility. Inclusion complexes of pioglitazone HCl were prepared with Î²-cyclodextrin using various methods (physical mixing, kneading method, co-precipitation). The main aim of the present invention is to study the effect of the method of preparation on the dissolution profiles of pioglitazone HCl-Î²-Cyclodextrin inclusion complexes. The phase solubility profile of pioglitazone HCl with Î²-cyclodextrin was classified as AL-type and stability constant with 1:1 molar ratio was 115.45, calculated from the phase solubility diagram. Formation of the inclusion complex between pioglitazone HCl and Î²-cyclodextrin was confirmed by the Fourier Transform Infrared (FT- IR) spectroscopy. The dissolution profile of inclusion complexes were determined and compared with those of pioglitazone HCl alone and its physical mixtures.The dissolution rate of the pioglitazone HCl-Î²-cyclodextrin inclusion complex prepared by the co-precipitation method was six times higher when compared with the pure drug. The method of complexation of pioglitazone HCl in Î²-CD increased the dissolution rate of the drug in the following order: Coppt > KM > PM >Drug.